2017
DOI: 10.1111/nyas.13331
|View full text |Cite
|
Sign up to set email alerts
|

The neuroscience of people watching: how the human brain makes sense of other people's encounters

Abstract: Neuroscientific investigations interested in questions of person perception and impression formation have traditionally asked their participants to observe and evaluate isolated individuals. In recent years, however, there has been a surge of studies presenting third-party encounters between two (or more) individuals as stimuli. Owing to this subtle methodological change, the brain's capacity to understand other people's interactions and relationships from limited visual information--also known as people watch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 133 publications
(415 reference statements)
3
69
0
Order By: Relevance
“…5 and 6; see also ref. 7 for a review of related studies), but have not provided evidence for the selectivity of this response. Two other studies (8,9) found activations in numerous brain regions when people viewed social interactions between two humans vs. two humans engaged in independent activities, both depicted with point-light stimuli.…”
Section: E114 | Wwwpnasorgmentioning
confidence: 99%
“…5 and 6; see also ref. 7 for a review of related studies), but have not provided evidence for the selectivity of this response. Two other studies (8,9) found activations in numerous brain regions when people viewed social interactions between two humans vs. two humans engaged in independent activities, both depicted with point-light stimuli.…”
Section: E114 | Wwwpnasorgmentioning
confidence: 99%
“…Of course, these regions do not represent discrete animate and inanimate categories, but instead are responsive to a wide variety of stimuli . Activity within these regions appears to index an observed agent's features (e.g., facial features, body posture, and motion), the interactive nature of the situation, context, and perceived animacy and socialness . The AON comprises frontoparietal regions spanning the posterior inferior frontal gyrus and inferior parietal lobule, which are engaged in a similar manner for executed and observed actions .…”
Section: The Attribution Of Socialnessmentioning
confidence: 99%
“…For example, in a behavioral response task it was found that individuals with spider phobia exhibited more rapid visual orienting responses (automatic approach) to spider-related stimuli, but then avoided looking at these negative/affective stimuli compared with a non-anxious control group, reflecting a visual scanning pattern termed vigilance-avoidance (Rinck and Becker, 2007). This novel study also highlights an additional distinction which has emerged in the field, i.e., the recognition that aversive stimuli can be either social (e.g., human actions) or non-social (e.g., aggressive animals such as angry dogs and snakes) in nature (for a review see Van Overwalle, 2009; for a recent review on the topic see also Quadflieg and Koldewyn, 2017). …”
Section: Introductionmentioning
confidence: 83%